Determinants of the tourism activity of school pupils (aged 15-19) from Słupsk and Częstochowa - Krzysztof Parzych (Tourism, 2010)
The purpose of this article is to describe the different types of tourism undertaken by school pupils (aged 15–19) through the example of their tourism trips. Two cities were used: Słupsk and Częstochowa. Analyses of the differing forms of tourism have been made in the context of geographical, socio-economic and demographic determinants for both cities.